Improving of the logistic process in the warehouse using lean-technologies - Gaftuniak, Anastasia Mykolayivna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The present paper investigates how the Lean philosophy can be used in Warehousing businesses. The research showcases the implementation of three Lean tools, such as 5S, Value stream mapping and Pull system in the warehouse. Documented studies to improve stock management in small-sized enterprises are not common in the literature. The objective of this research is to examine how Lean thinking may be applied to the warehousing process, investigate the most effective Lean tools that can improve warehouse operations and give guidelines concerning the choice of tool that can be used to further leverage Lean Production in Warehousing. The empirical part of this paper is conducted as an ABC-analysis in manufacturing company. The primary source of information will be the review of the firm's databases. The results of the study imply that implementation of Lean system will allow the company to reduce costs, optimize warehouse operations, minimize labor, and as a result, improve the competitiveness in the market.